Occupational Matrilineages in the Printing House: Petitions for Licenses as a Source for Scholarship on Early Modern Women - Wyffels, Heleen (Early Modern Low Countries, 2025)
The application dossiers for printer’s licences and privileges from the Privy Council in Brussels are a well-known source for book historians. To increase their chances of success, printers used a range of different arguments in their requests, including a family tradition in the trade. Using the application dossiers of the Boscard and Serrurier families in seventeenth-century Saint-Omer and Douai, I show that women frequently appeared in the applicants’ occupational lineage histories and that women printers also used family history as an argument in their own applications. These sources help us to rewrite the patrilinear narratives about the early modern printing business.